1987
DOI: 10.1093/nar/15.19.8023
|View full text |Cite
|
Sign up to set email alerts
|

Synonymous codon usage inBacillus subtilisreflects both translational selection and mutational biases

Abstract: Codon usage data for 56 Bacillus subtilis genes show that synonymous codon usage in B. subtilis is less biased than in Escherichia coli, or in Saccharomyces cerevisiae. Nevertheless, certain genes with a high codon bias can be identified by correspondence analysis, and also by various indices of codon bias. These genes are very highly expressed, and a general trend (a decrease) in codon bias across genes seems to correspond to decreasing expression level. This, then, may be a general phenomenon in unicellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(177 citation statements)
references
References 47 publications
8
169
0
Order By: Relevance
“…The codon usage pattern closely resembles that reported for highly expressed B. subtilis proteins (57), which suggests that also the S-complex proteins are expressed at a high level.…”
Section: Methodssupporting
confidence: 76%
“…The codon usage pattern closely resembles that reported for highly expressed B. subtilis proteins (57), which suggests that also the S-complex proteins are expressed at a high level.…”
Section: Methodssupporting
confidence: 76%
“…Genes with high CAI values in fast-growing organisms are commonly interpreted as those which are involved in maintaining this growth rate or in enzymatic activities with a rapid response (Gouy and Gautier 1982;Sharp and Li 1987;Sharp et al 1988;Me´digue et al 1991;Shields and Sharp 1987;Carbone et al 2004). Genes with such properties are coding for ribosomal proteins, heat shock proteins, antioxidant proteins, proteins involved in the respiratory chain, structural genes (for eukaryotes), and enzymes involved in the metabolic pathways of amino acids biosynthesis.…”
Section: Metabolic Activities Derived From Cai Valuesmentioning
confidence: 99%
“…High expression rates of certain genes during exponential growth, or of enzymes involved in fundamental metabolic activities like glycolysis, have been very often reported in the literature for fast growers and studied, since the 1980s, through the notion of the Codon Adaptation Index (CAI) (Sharp and Li 1987). For fast-growing organisms like Escherichia coli and Saccharomyces cerevisiae, but also Caenorhabditis elegans and Dro-sophila melanogaster, genes have been ranked by CAI values and correlated with gene expression levels and functional activity (Sharp and Li 1987;Sharp et al 1986Sharp et al , 1988Shields and Sharp 1987;Stenico et al 1994). Carbone et al (2003) showed that the CAI can be defined purely by sequence analysis, that it can be calculated for genomes of organisms whose biological activities are not known, and that the resulting ranking of genes correlates well with the dominant codon bias of the organism.…”
Section: Introductionmentioning
confidence: 99%
“…The gene was designed based on the amino acid sequence of full-length SGPE by matching the codon preference of B. subtilis (Shields & Sharp, 1987;Wright, 1990). The full-length gene was prepared from 32 oligonucleotides using the overlap PCR technique (Higuchi, 1989).…”
Section: Construction Of a Synthetic Gene And Expression Vector For Sgpementioning
confidence: 99%
“…The DNA sequence was designed to match the codon preference of B. subtilis (Shields & Sharp, 1987;Wright, 1990), i.e., the G/C-content of the gene was altered from 94% G/C on the third position of the codon to 49%. Incorporation of a large number of unique restriction sites allowed easy mutagenesis of the gene (see below).…”
Section: Construction Of a Synthetic Gene For Sgpementioning
confidence: 99%